The roots of a quadratic equation are given as 6 and 7. This means that x - 6 = 0 and x - 7 = 0

We can write ( x - 6)( x - 7) = 0

=> x^2 - 6x - 7x + 42 = 0

=> x^2 - 13x + 42 = 0

Therefore the required quadratic equation is

**x^2 - 13x + 42 = 0**

The roots of a quadratic equation are given as 6 and 7. This means that x - 6 = 0 and x - 7 = 0

We can write ( x - 6)( x - 7) = 0

=> x^2 - 6x - 7x + 42 = 0

=> x^2 - 13x + 42 = 0

Therefore the required quadratic equation is

**x^2 - 13x + 42 = 0**